TECHNOLOGICAL FEATURES OF LABORATORY CULTIVATING TELENOMUS (TELENOMUS VERTICILATUS KIEFFER, 1917), PINE MOTH PARASITE (DENDROLIMUS PINI L.) - Karpovich, M. S.; Drozdа V. F. (Scientific Progress & Innovations, 2020)
Due to worsening climatic conditions, decreasing the amount of ground waters in forests there is a con-siderable weakening of tree species, especially in plantations of common pine. Warm winters and warm, sunny and dry weather in the spring favor the development and spreading of coniferous stand chewing phy-tophages. .One of the most dangerous is pine moth (Dendrolimus pini L.). Studies have shown that pine plan-tations in Polissia are often damaged by pine moth, the caterpillars of which cause defoliation of needles resulting in various physiological abnormalities, namely: retardation in trees’ growth and development, and sometimes their shrinkage. Based on expert analysis of literature sources and own research, the article presents defining biological and ecological features related to telenomus spreading and development. It has been established that telenomus females parasitize on eggs of pine moth in the middle and upper part of the crown, as well as on the edge of the forest and inside the quarters. According to the analysis of primary sources, the prospects of pine stands’ protection from pine moth using biological methods have been shown. The most common parasites of pine moth eggs are telenomus and trichogramma. The infection rate of eggs with natural populations ranged from 7.8 to 22.4 %. These figures show the expediency of the method of la-boratory cultivating with subsequent disseminating laboratory cultures of trichogramma and telenomus in pine plantations. The study was conducted during 2016–2019 in Polissia pine woodlands and laboratory conditions. The following generally accepted methods in entomology, parasitology, and bio-technology were used during the experiments – monitoring studies, visual, instrumental and physiological monitoring of pine moth populations, the methods of cultivation and dissemination of laboratory cultures of trichogramma and telenomus on trees. The terms, rates and multiplicity of parasite dissemination have been substantiated. The presented results show quite a significant regulating role of natural entomophages in population dynamics of pine moth and the prospects of artificial spreading the females of laboratory cultures of trichogramma and telenomus in pine plantations. For the first time the technology of mass laboratory cultivation of Telenomus verticillatus Kieffer for the needs of biological protection of pine plantations from pine moth has been proposed.